KAJIAN ISLAM KLASIK TERHADAP FAKTOR-FAKTOR RISIKO UNDERWRITING PADA ASURANSI JIWA SYARIAH DALAM MENGEMBANGKAN BAURAN PEMASARAN - Achmad, Basuki (Sekolah Tinggi Ilmu Fikih Syeikh Nawawi Tanara Serang, 2021)
This study aims to determine the underwriting risk factors that will influence the decision to continue or change the underwriting policy in Sharia Life Insurance. known for underwriting which assesses age, place of residence and several other factors will be studied by finding it in some classic Islamic books.